2016
DOI: 10.1111/trf.13658
|View full text |Cite|
|
Sign up to set email alerts
|

Red blood cell transfusion triggers in acute leukemia: a randomized pilot study

Abstract: BACKGROUND Red blood cell (RBC) transfusion thresholds have yet to be examined in large randomized trials in hematologic malignancies. This pilot study in acute leukemia uses a restrictive compared to a liberal transfusion strategy. STUDY DESIGN AND METHODS A randomized (2:1) study was conducted of restrictive (LOW) hemoglobin (Hb) trigger (7 g/dL) compared to higher (HIGH) Hb trigger (8 g/dL). The primary outcome was feasibility of conducting a larger trial. The four requirements for success required that m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
62
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(66 citation statements)
references
References 27 publications
3
62
1
Order By: Relevance
“…Incidence of bleeding was reported by four studies (Jansen et al , ; Webert et al , ; Berger et al , ; DeZern et al , ). No differences in the occurrence of any bleeding or clinically significant bleeding were found between the liberal and restrictive RBC transfusion group in a study of 60 patients (120 g/l vs. 80 g/l), RR 1·05 (95% CI 0·87–1·26) and RR 0·94 (95% CI 0·69–1·27) (Webert et al , ).…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…Incidence of bleeding was reported by four studies (Jansen et al , ; Webert et al , ; Berger et al , ; DeZern et al , ). No differences in the occurrence of any bleeding or clinically significant bleeding were found between the liberal and restrictive RBC transfusion group in a study of 60 patients (120 g/l vs. 80 g/l), RR 1·05 (95% CI 0·87–1·26) and RR 0·94 (95% CI 0·69–1·27) (Webert et al , ).…”
Section: Resultsmentioning
confidence: 98%
“…Tables and provide information on the bias risk assessment. Two RCTs were classified as ‘low risk of bias’ (Webert et al , ; DeZern et al , ). A lack of blinding in the RCT reported by DeZern et al () was allowed as blinding in transfusion studies is almost impossible.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The transfusion criteria used in AL patients in this audit were mostly similar to those used for the general population. Although Hb transfusion thresholds in hematologic malignancy patients have not been universally agreed upon, two small randomized clinical trials have evaluated the use of a restrictive Hb threshold (7 g/dL) in AL patients and found that it led to noninferior outcomes more than did a higher threshold (8–9 g/dL) . Larger trials are needed to standardize restrictive transfusion thresholds in AL patients according to the clinical scenario.…”
Section: Discussionmentioning
confidence: 99%
“…In the second trial, DeZern et al . randomized patients receiving induction therapy to a red cell transfusion threshold of 70 g/l or 80 g/l . Of note, the liberal transfusion in this pilot trial used the same transfusion threshold as the restrictive transfusion strategy in the previous trial.…”
Section: Current Clinical Evidence For Restrictive Red Cell Transfusimentioning
confidence: 99%